Implementasi Supervisi Akademik dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam pada Guru SLB Negeri Lamongan - Rosyidah, Fatihatur; Fathurrahman, Fathurrahman (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
Academic supervision is a key responsibility of school principals in enhancing the quality of teaching, including in Islamic Religious Education (PAI) at Special Needs Schools (SLB), where students exhibit diverse characteristics. This study aims to describe the implementation of academic supervision carried out by the principal toward PAI teachers, as well as the improvement steps taken by these teachers to enhance the quality of instruction at SLB Negeri Lamongan. A qualitative descriptive approach was used, with data collected through observation, interviews with the principal and PAI teachers, and documentation. The findings indicate that academic supervision is conducted systematically each semester, beginning with planning activities such as setting goals, scheduling, preparing lesson plans by teachers, and designing observation tools by the principal. Supervision is carried out individually through classroom visits and collaboratively. The evaluation and follow-up stages include reflective meetings, in-depth discussions with PAI teachers, and specialized training to improve their teaching competence. In response, PAI teachers engage in professional discussions with peers, actively participate in teacher working groups (MGMP) and training programs, and integrate the acquired recommendations and knowledge into their teaching practices.